The physicochemical, sensory evaluation and glycemic load of stingless bee honey and honeybee honey - Abdul Manam M. (2024)
Honey is a widely consumed functional food which has a valued place in traditional medicine. The purpose of this study was to compare the physicochemical properties, sensory evaluation, and glycemic load of honeybee honey and stingless bee honey. Physicochemical parameters include moisture, ash, pH, free acidity, electrical conductivity and sugar content which were determined by following the International Honey Commission methods. Ten subjects were selected for glycemic index study. For oral glucose tolerance test (OGTT), about 50 g of pure glucose in 250 mL of water was given to subject while 25 g of pure glucose in 250 ml water as a reference food. The blood glucose response was measured based on the incremental area under curve (IAUC) and compared to that of 25 g of available carbohydrate from glucose. Results indicated that the moisture content (29.5% vs 28.0%), free acidity (84.5 vs 73.5) and total carbohydrate (64.33 vs 50.35) of honeybee honey was significantly (all p<0.05). Their ash content is closely similar, which might be due to a similar geographical source, namely the Marang area. In terms of sensory evaluation, honeybee honey is more preferred, as the overall scores (5.5 vs 4.8) including colour (4.5 vs 3.5), odour (5.2 vs 4.0) and sweetness (6.0 vs 3.5) were significantly higher than stingless bee honey, even though the aftertaste (5.8 vs 4.8) is also higher. Furthermore, stingless bee honey has lower GI and GL (81.76, 5.27) as compared to honeybee honey (97.86, 6.96), respectively. It is suggested that the serving in term of odd or even numbers might affect the outcomes of the study as honeybee honey represents four spoons vs five spoons of stingless bee honey.